1997
DOI: 10.1039/a607646g
|View full text |Cite
|
Sign up to set email alerts
|

The ‘inverse electron-demand' Diels–Alder reaction in polymer synthesis. Part 4.1 The preparation and crystal structures of some bis(1,2,4,5-tetrazines)

Abstract: Reaction of 3,6-bis(3,5-dimethylpyrazolyl)-1,2,4,5-tetrazine with mono-and di-amines gives rise to nucleophilic substitution of one or both of the pyrazolyl substituents, and reaction with diamines under appropriate conditions can lead to bis(3-amino-1,2,4,5-tetrazines), e.g. 12a, 12b and 13. The crystal structures of two of these (12a and 13) show electronic interaction between the tetrazine rings and the amino groups, but none between the tetrazine and pyrazole rings. In 12a there is an extensive network of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Inverse electron demand Diels-Alder reaction of 1,2,4,5-tetrazines are well known in the literature. Cycloadditions with electron-rich alkynes [759,762,774,776,[781][782][783][784][785][786][787][788] or alkenes [602,762,772,773,781,784,[789][790][791][792] Zhou et al have described an alternative Diels-Alder route to the well-known C,C cycloaddition (Carboni-Lindsey reaction). Quantum mechanical calculations showed that N,N cycloaddition of alkenes and alkynes to s-tetrazines is possible.…”
Section: Reactions With Nucleophilic Reagentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Inverse electron demand Diels-Alder reaction of 1,2,4,5-tetrazines are well known in the literature. Cycloadditions with electron-rich alkynes [759,762,774,776,[781][782][783][784][785][786][787][788] or alkenes [602,762,772,773,781,784,[789][790][791][792] Zhou et al have described an alternative Diels-Alder route to the well-known C,C cycloaddition (Carboni-Lindsey reaction). Quantum mechanical calculations showed that N,N cycloaddition of alkenes and alkynes to s-tetrazines is possible.…”
Section: Reactions With Nucleophilic Reagentsmentioning
confidence: 97%
“…The electron-deficient aromatic ring of tetrazine and its reactivity towards nucleophiles have been utilized in the preparation of non-symmetrically substituted tetrazines by substitution of leaving groups, such as chloro [770,771], methylthio [770,[772][773][774][775] or dimethylpyridazolyl [755,757,776,777] with nitrogen, oxygen or sulfur nucleophiles. The use of carbon nucleophiles, such as organolithium or Grignard reagents, with 3,6-disubstituted 1,2,4,5-tetrazines 368 led to the addition of an organic group onto a ring nitrogen atom to afford 1,4-dihydrotetrazines 369 [778] (Scheme 20.109).…”
Section: Reactions With Nucleophilic Reagentsmentioning
confidence: 99%
“…The reactions of [1,2,4]triazolo [4,3-b] [1,2,4,5]tetrazines with nucleophilic reagents have so far been scarcely investigated. It has been reported that the 3,5-dimethylpyrazolyl substituents in [1,2,4]triazolo [4,3-b] [1,2,4,5]tetrazines can easily be displaced with aliphatic amines or alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Also, some carbon modifications of 1,2,4,5-tetrazines due to displacement reactions with anhydro bases of quinaldinium salts [8] and heterocyclic carbenes [9] or by cross-coupling reactions with arylboronic acids [10] and acetylenes [11] have been reported. There are also examples where instead of nucleophilic substitution reactions at C-3 or C-6, azaphilic addition [12,13] or [4+2]cycloaddition reactions [8,14] have been observed to give rise to the corresponding 1,4-dihydrotetrazines or pyridazine derivatives, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The product distribution was interpreted on the basis of quantum chemical calculations. The triazolotetrazinium salts (9,10a-b) were found to dealkylate on workup to give the corresponding tetrafluoroborate salts (7,8). …”
mentioning
confidence: 99%